Feasibility of Left Atrial Appendage Closure in Atrial Fibrillation Patients with a History of Intracranial Bleeding: A Systematic Review of Observational Studies - Muhammad Ajmal; Qurat Ul Ain Riaz Sipra; Cristina Pecci; Nusrum Iqbal; Sulaiman Rathore (Journal of Interventional Cardiology)
Background. Left atrial appendage occlusion (LAAO) is performed in patients with nonvalvular atrial fibrillation to reduce the risk of ischemic stroke. The patients with a history of intracranial hemorrhage were excluded from the pioneer randomized controlled trials. The purpose of this systemic review was to evaluate the data from observational studies reporting the efficacy and safety of LAAO in patients with a history of intracranial hemorrhage. Methods. Ovid MEDLINE, Embase, Cochrane Central Register of Controlled Trials, Web of Science Core Collection, Scopus, Global Index Medicus, and ClinicalTrials.gov data sources were utilized for data collection. Results. A total of 12 studies met the inclusion criteria that included seven retrospective observational and five prospective observational studies. A total of seven hundred and twenty-seven patients with a history of intracranial hemorrhage underwent percutaneous left atrial appendage occlusion. There were 11 events of recurrent intracranial hemorrhage, 12 ischemic strokes, 4 transient ischemic attacks, and 26 all-cause deaths. The duration of follow-up varied from 3 months to 3.6 years in the included studies. Conclusion. Left atrial appendage occlusion can potentially be an effective and relatively safe treatment option to reduce the risk of ischemic stroke in selected patients with nonvalvular atrial fibrillation patients and history of intracranial hemorrhage. Future prospective randomized trials are needed to validate this approach.